Institutionalising Ritual and Local Authority in Pilgrimage to a Sacred Tomb: A Case Study of Ngadirojo Village, Gladagsari Subdistrict, Boyolali Regency - Yulia Indriyani (Lakpesdam PCNU Kota Salatiga, 2023)
This article examines pilgrimage (ziyarah) to the Sacred Tomb of Mundhing in Ngadirojo Village, Gladagsari Subdistrict, Boyolali Regency, and assesses its implications for local Islamic creed (ʿaqīdah). Conceptually, grave visitation in Islam functions as a religious practice aimed at praying for the deceased, fostering eschatological awareness, and strengthening moral–spiritual orientation; however, in lived religious settings it may intersect with pragmatic motives and local symbols that can generate theological ambiguity in the absence of adequate creedal literacy. Accordingly, the study addresses the following questions: how the tomb’s sacredness is constructed and reproduced; how the pilgrimage rites/etiquette and the custodian (juru kunci) regulate practices to remain within the bounds of tawḥīd; how pilgrims’ dominant motives (educative–eschatological vs. instrumental–pragmatic) relate to experiences of “mustajab/blessing” and to the use of wasīlah/tawassul; how pilgrimage affects ʿaqīdah (both strengthening tawḥīd and posing risks of deviation); and how boundary mechanisms operate to prevent pilgrimage from shifting into cultic veneration. Employing a qualitative descriptive approach, the research draws on interviews with community members and pilgrims, complemented by an interpretation of the socio-ritual context to capture meanings, motivations, and local regulation. The findings indicate that the sacred status of the Mundhing tomb is produced through collective memory, saintly narratives, and the institutionalisation of ritual space (e.g., pavilion, prayer room, and designated prayer area); pilgrimage practices are guided by etiquette and by restrictions on high-risk symbols (e.g., incense), which the custodian reinforces as a boundary mechanism; pilgrims’ motives range from worshipful self-reflection (muḥāsabah) to worldly petition in which Mundhing is positioned as a wasīlah; and the impact on ʿaqīdah is dual—pilgrimage strengthens tawḥīd when supplication and reliance remain directed to Allah (SWT) and the visit functions as a space for reflection and moral exemplarity, yet it may incline toward shirk when “mustajab” is construed as an inherent power of the tomb/the deceased, making the effectiveness of ritual governance and communal tawḥīd literacy decisive for keeping the practice within orthodox creedal boundaries.